Opposing Electronic and Nuclear Quantum Effects on Hydrogen Bonds in H2O and D2O - Clark, Timothy; Heske, Julian; Kühne, Thomas D. (ChemPhysChem, 2019)
The effect of extending the O-H bond length(s) in water on the hydrogen-bonding strength has been investigated using static ab initio molecular orbital calculations. The "polar flattening" effect that causes a slight sigma-hole to form on hydrogen atoms is strengthened when the bond is stretched, so that the sigma-hole becomes more positive and hydrogen bonding stronger. In opposition to this electronic effect, path-integral ab initio molecular-dynamics simulations show that the nuclear quantum effect weakens the hydrogen bond in the water dimer. Thus, static electronic effects strengthen the hydrogen bond in H2O relative to D2O, whereas nuclear quantum effects weaken it. These quantum fluctuations are stronger for the water dimer than in bulk water.
CRIS-Team WoS Importer:2019-10-01